2020
DOI: 10.1101/2020.07.24.220137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hijacking of the host cell Golgi byPlasmodiumliver stage parasites

Abstract: The intracellular lifestyle represents a challenge for the rapidly proliferating liver stage Plasmodium parasite. In order to scavenge host resources, Plasmodium has evolved the ability to target and manipulate host cell organelles. Using dynamic fluorescence-based imaging, we show a direct interplay between the pre-erythrocytic stages of Plasmodium berghei and the host cell Golgi during the entire liver stage development. Liver stage schizonts fragment the host cell Golgi into miniaturized stacks, which incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 105 publications
(131 reference statements)
2
2
0
Order By: Relevance
“…6A). Consistent with other reports (De Niz et al, 2020;Raphemot et al, 2019), we also observed Golgi localized to the PVM (Fig. 6A).…”
Section: Host Golgi and Intracellular Vesicles Interact With Plasmodium Liver Stagesupporting
confidence: 93%
See 1 more Smart Citation
“…6A). Consistent with other reports (De Niz et al, 2020;Raphemot et al, 2019), we also observed Golgi localized to the PVM (Fig. 6A).…”
Section: Host Golgi and Intracellular Vesicles Interact With Plasmodium Liver Stagesupporting
confidence: 93%
“…We observed colocalization between intracellular vesicles and the PVM (Fig. 6B and C), consistent with other reports (De Niz et al, 2020;Raphemot et al, 2019). The colocalization of intracellular vesicles with the PVM was greatly reduced after brefeldin-A treatment (Fig.…”
Section: Host Golgi and Intracellular Vesicles Interact With Plasmodium Liver Stagesupporting
confidence: 92%
“…As an intracellular obligatory parasite, Plasmodium manipulates its host cell to facilitate infection. Plasmodium EEFs were shown to siphon host biomolecules while evading autophagic clearance through exclusion of host phagophore components (Agop-Nersesian et al, 2017;De Niz et al, 2020;Fouge `re et al, 2016;Itoe et al, 2014;Lopes da Silva et al, 2012;Meireles et al, 2017;Petersen et al, 2017;Posfai et al, 2018;Real et al, 2018;Thieleke-Matos et al, 2016;Vijayan et al, 2020). Likewise, a deregulation of host homeostatic pathways was described in Plasmodium-infected hepatocytes, which includes a desynchronization in host RPS6 phosphorylation upon insulin stimulation (Glennon et al, 2019;Kaushansky et al, 2013) and the suppression of AMPK activity despite nutrient loss in the host (Ruivo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…P. berghei showed associations of the PVM with Golgi membranes that were maintained throughout the proliferation stage in hepatocytes and followed by Golgi rearrangements to expand membrane interactions which are proposed to improve the parasites nutritional supply. The small GTPase RAB11 is crucial for the organelle’s morphological changes during P. berghei infections, as functional mutations diminished this effect [ 103 ]. RAB11 takes part in the translocation of trans-Golgi vesicles to cellular target membranes and therefore represents an important element of the secretory pathway [ 104 ].…”
Section: Membrane-bound Organelles Manipulated By Intracellular Pathogensmentioning
confidence: 99%